The Effects of Expert and Augmented Feedback on Learning a Complex Medical Skill. Issue 4 (August 2020) - Cecilio-Fernandes, Dario; Cnossen, Fokie; Coster, Jenifer; Jaarsma, AD (Debbie) C.; Tio, René A.
Many medical skills are complex due to their requirements for integration of declarative (biomedical) knowledge with perceptual–motor and perceptual–cognitive proficiency. While feedback generally helps learners guide their actions, it is unclear how feedback supports the integration of declarative knowledge with skills. Thus, we investigated the effect of expert and augmented feedback on acquisition and retention of a complex medical skill (acquiring a transthoracic echocardiogram) in a simulation study. We randomly assigned 36 medical undergraduate students to one of three feedback sources: Expert (EF), Augmented visual (HS), and Expert plus Help Screen (EF + HS). Participants practiced until reaching proficiency. Outcome measures (knowledge test and practical skill ratings on a 5-point scale), were gathered at initial acquisition and at retention after 11 days, the time needed to obtain the images and the quality of images obtained. We divided the knowledge test into three topics: names of the images, manipulation of the probe, and anatomy of the heart. At acquisition, immediately after training, EF group participants were faster at obtaining images than participants in the two other groups. On the retention test, there were no group differences for speed of obtaining images, but the EF + HS group scored significantly higher than the other two groups on image quality. Thus, expert feedback best assisted initial acquisition and combined augmented and expert feedback best assisted retention of this complex medical task. Expert assistance reduced learners' cognitive load during initial practice, helping learners integrate declarative knowledge with physical skills.